A New Method for the Synthesis of Cobalt Complex of Tetra-2, 3-(5-tert-butyl-pyrazino) porphyrazine. Issue 1 (March 2021) - Wang, Dejun; Li, Hui; Jiang, Xiren; Zhao, Chaocheng
Abstract: A two-step synthesis of cobalt complex of tetra-2, 3-(5- tert -butyl-pyrazino) porphyrazine as porphyrazine derivatives carrying six-membered pyrazine rings annulated at the periphery of the tetrapyrrolic macrocycle was described starting from 3, 3-dimethyl-2-butanone, selenium dioxide, 2, 3-diaminomaleonitrile, metal salts, and urea. In comparison with the previously reported multistep procedure, this new multicomponent protocol for the preparation of synthetically, biologically, and technologically relevant tetra-2, 3-(5- tert -butyl-pyrazino) porphyrazine includes some important aspects like the fast and simple reaction, easy workup procedure, and high atom economy.